Determinants of competitive advantage in the tourism sector of Langkawi Island, Kedah / Er Ah Choy Nur and Helwa Ruslan - Nur, Er Ah Choy; Ruslan, Helwa (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2018)
Langkawi is not just the focal point for ecotourism on the world tourism map, but it also has the potential to become an economic driver for the country. The development of ecotourism is a concept of development which emphasizes sustainability. This study was conducted to analyze the competitive advantage determinants in the ecotourism sector using the Porter Diamond Model. A survey based on a set of questionnaires was carried out with 300 tourists. The study found that the development of Langkawi's tourism products has attracted high demand from both domestic and international tourists with its physical characteristics and existing natural resources. Strong cooperation among Langkawi Island stakeholders will produce tourist, resulting a favourable perception of Langkawi island as the preferred ecotourism destination.